Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Boundary condition (Electromagnetics)

  1. Feb 6, 2006 #1
    I got some problem about using boundary conditions,especially in the fifth pics,those sentences marked by red.I really don't know how to use
    Js=An x H,since I don't know the fields well enough.Some questions of mine are illustrated in the sixth pic by different colors.

    I'm sorry the pics are so ugly.If someone can understand me,please give me some hints. It's too late and I must go to bed,I'll edit it tomorrow.Thanks!

    http://www.pixnet.net/displayimage.php?pid=28028953&fullsize=1&SID= [Broken]

    [PLAIN]http://www.pixnet.net/displayimage.php?pid=28030490&fullsize=1&SID= [Broken]

    [PLAIN]http://www.pixnet.net/displayimage.php?pid=28030490&fullsize=1&SID= [Broken]
    http://www.pixnet.net/displayimage.php?pid=28027945&fullsize=1&SID= [Broken]
    http://www.pixnet.net/displayimage.php?pid=28027979&fullsize=1&SID= [Broken]
    http://www.pixnet.net/displayimage.php?pid=28029476&fullsize=1&SID= [Broken]
    Last edited by a moderator: May 2, 2017
  2. jcsd
  3. Feb 7, 2006 #2
    Well, do you know how these boundary conditions are derived ? What is the theory behind that ? I don't understand what you mean by

    "I really don't know how to use
    Js=An x H,since I don't know the fields well enough"

    Are you saying you do not know the H-field in this situation ? I mean it is derived in the pictures you show us. Or are you asking why this boundary condition is valid or how you acquire it's formula ? To answer that, try answering my first question to you.

    You need to be a bit more specific, please.

  4. Feb 7, 2006 #3
    In the last two pic,it said that Hy0 satisfied Js=An x H at z=-L.

    My most confused question is,why doesn't author choose z=0?
    I guess the boundary in consideration is x=0,
    then at z=0,x<0 Hy0 exists,x>0 Hy0=0

    This situation is the same as at z=-L,x<0 Hy0 exist ,x>0 Hy0=0.isn't it?

    And Hy0 is not varying with z,so Hyo at z=0 should be the same as Hy0 at z=-L.So I think at z=0 Hy0 might aslo satisfied Js=An x H.

    But if Hy0 satisfied Js=An x H at z=0,which means Hy2=0 at z=-L,then by (5.98),C=0,a different answer.

    I must be somewhere wrong,I really want to find it out.@@

    Thanks for attention.
    Last edited: Feb 7, 2006
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook